Effect of the primer on barcode quality in ink-jet printing - Khadzhynova, Svitlana (Eastern-European Journal of Enterprise Technologies, 2020)
It has been proposed to modify the surface of offset and coated paper with a special coating (primer) that ensures the high quality of ink-jet printing, specifically barcodes. The application of digital ink-jet printing using aqueous-based inks makes it difficult to achieve the required print quality on conventional paper. Ink-jet printing is widely used in the production of customized packaging and labeling products. Given that this type of products contains the printed barcode, it is necessary to ensure its functionality (readability) after printing. The primer ensures a controlled process of ink absorption at ink-jet printing, thereby improving the print quality. To this end, a composition of the primer was used on the basis of a water solution of the interpolymeric complex of polyvinyl alcohol (PVOH) and polyvinylpyrrolidone (PVP). The influence of the primer that contains different amounts of the interpolymeric complex on a change in the water contact angle of imprinted paper has been investigated. Prints on paper with and without the primer were obtained using an ink-jet printing method; quality of the line and barcode print was assessed. Such quality indicators for the line were defined as a line width on the imprint, a line blurriness at the line-paper interface, a line raggedness, and the optical density. In addition, the primer’s effect on the barcode print quality at ink-jet printing was investigated. The study results make it possible to ensure the high quality of barcode printing on conventional print papers by using an ink-jet printing method. Applying the primer improves the line and barcode print quality. The barcode quality grade increases from the lowest (unacceptable) score of 0 (F) on paper without a primer to a score of 2 (C) on paper with the primer, which warrants that it is readable on packaging by a scanner.